Somatic features in women employed in chemical and clothing works of upper Silesian industrial district - Majchrzyk, Helena (Anthropological Review, 1986)
The analysis of the experimental material aimed at giving the answer to the question, what were the trends of shaping somatic features in women representing the two professional groups employed in the area of the Upper Silesian Industrial District. The study was carried on 468 work-women in the productive ages (20 - 59 years) employed in chosen chemical and clothing works of Katowice Province. The experimental material was divided into four decade-groups, joining the women in pairs according to their calendar age. 17 somatic features were measured and on their basis five indices of body structure were estimated. The results of the analysis has shown that both compared professional groups, over the whole period of the observation, do not present any clear differentiation in all the somatic features and the indices of body structure estimated on their basis.